Anti-thrombotic therapy in infective endocarditis. (September 2011) - Vanassche, Thomas; Peetermans, Willy E; Herregods, Marie-Christine; Herijgers, Paul; Verhamme, Peter
Despite advances in medical and surgical treatment, infective endocarditis (IE) still carries a high risk of morbidity and mortality. One of the determinants of an adverse outcome is the presence of systemic embolization and in particular, of CNS embolization. IE vegetations consist of bacteria, platelets and inflammatory cells in a fibrin mesh. The interactions between pathogens, platelets and the coagulation system are critical to vegetation initiation and growth. This understanding has led to the study of the effect of anti-thrombotic treatment on IE vegetation formation and embolization. Although it has been demonstrated that antiplatelet and anticoagulant strategies have an impact on in vitro and animal models of IE, results from the available clinical studies are conflicting. In this article, we provide an overview of the available experimental and clinical data on anti-thrombotic treatment in IE and summarize the current guidelines. An early diagnosis, prompt empiric antibiotic treatment and a careful selection of patients who benefit from early surgical intervention remain essential in the prevention of embolic complications. In patients who have other indications for antiplatelet or anticoagulant treatment, the continuation of this treatment is deemed safe in the absence of hemorrhagic complications.